DIGITAL MATHEMATICS LEARNING COMPANION (DMLC): APLIKASI ANDROID GURU PENDAMPING KHUSUS MATEMATIKA BAGI PENYANDANG TUNANETRA BERBASIS SUARA - Clara Fatimah; Dwi Parinata; Arieska Efendy; Yuli Santika (Jurnal Ilmiah Mahasiswa Matematika Realistik, 2021)
Based on Law no. 20 of 2003 education is the right of all Indonesian citizens, including persons with disabilities, especially in this article, namely people who are blind. The research objective is to develop technology-based teaching media for blind people. The learning media developed will help blind people learn mathematics independently like normal people in utilizing the sophistication of existing technology for independent learning. The application will be called Digital Mathematics Learning Companion (DMLC). DMLC is an application on the Android platform that is intended as a companion teacher for the visually impaired in learning mathematics. The DMLC application is an application on the Android platform that was developed with the facility of using voice both from instructions and commands to run the application. The application also allows users whose targets are visually impaired students to learn independently without being assisted by a special assistant teacher and run the application as a whole using voice commands and tap assistance as another alternative. In addition, users who cannot write braille can take advantage of this application to repeat the material until the user understands the material presented. The DMLC application can work optimally and effectively.Keywords: Android Application, DMLC, Blind